Contagion effect of quantitative easing policies in international financial markets - Delgadinho, Hugo Miguel da Silva (2022)
The following dissertation will present an analysis of the intra- and inter-regional impacts of the Quantitative Easing (QE) policies announcements on the appearance of price bubbles in the financial international markets, namely, United States of America, United Kingdom, Japan, and Eurozone. First, we have employed the Generalized Supremum Augmented Dickey-Fuller/Backward Supremum Augmented Dickey-Fuller (GSADF/BSADF) test (Phillips et al., 2015), to determine if there were in fact bubbles being created from 1995 to 2021 using daily observations of financial market indexes. Secondly, using a Vector Autoregressive (VAR) model with monthly observations from 1998 until 2021, we tested if QE announcements were impacting the chance of appearing price bubbles, including additionally for the analysis a set of control variables. Results suggest that there are several periods of explosivity in the markets for all 4 regions being in scope, especially during the periods between 2005 and 2015. Secondly, findings show that for the US there is strong evidence that these announcements decrease the chance of price explosiveness. However, in Eurozone and UK there is some evidence of the contrary effect. For Japanese markets there is no evidence of effects. Additionally, for all markets there is clear evidence of cross-regional effects being the most influential central bank the ECB affecting all regions except Japan, giving us the suggestion that the announcements could have widespread repercussions. At last, considering only the control variables, the interest rate is the variable that demonstrates the biggest influence in development of explosivity in the markets.